Campanian-Eocene dinoflagellate cyst biostratigraphy in the Southern Andean foreland basin: Implications for Drake Passage throughflow - Bijl, Peter K.; Guerstein, Gladys Raquel; Sanmiguel Jaimes, Edgar A.; Sluijs, Appy; Casadio, Silvio Alberto; Valencia, Víctor; Rodriguez Amenabar, Cecilia; Encinas, Alfonso (Andean Geology)
The tectonic opening of the Tasmanian Gateway and Drake Passage represented crucial geographic requirements for the Cenozoic development of the Antarctic Circumpolar Current (ACC). Particularly the tectonic complexity of Drake Passage has hampered the exact dating of the opening and deepening phases, and the consequential onset of throughflow of the ACC. One of the obstacles is putting key regional tectonic events, recorded in southern Patagonian sediments, in absolute time. For that purpose, we have collected Campanian-Eocene sediment samples from the Chilean sector of Southern Patagonia. Using U-Pb radiometric dating on zircons and dinoflagellate cyst biostratigraphy, we updated age constraints for the sedimentary formations, and the hiatuses in between. Thick sedimentary packages of shallow-marine and continental sediments were deposited in the foreland basin during the early Campanian, mid-Paleocene, the Paleocene-Eocene boundary interval and the middle Eocene, which represent phases of increased foreland subsidence. We interpret regional sedimentary hiatuses spanning the late Campanian, early-to mid-Paleocene, mid-Eocene and latest Eocene-early Oligocene to indicate times of reduced foreland subsidence, relative to sediment supply. We relate these changes to varying subduction rates and Andean orogeny. Dinoflagellate cyst assemblages suggest that the region was under the influence of the Antarctic-derived waters through the western boundary current of the Subpolar Gyre, developed in the southwest Atlantic Ocean and thus argues for limited throughflow through the Drake Passage until at least the latest Eocene. However, the proliferation of dinoflagellate endemism we record in the southwest Atlantic is coeval with that in the southwest Pacific, and on a species level, dinoflagellate cyst assemblages are the same in these two regions. This suggests that both regions were oceanographically connected throughout the early Paleogene, likely through a shallow opening of a restricted Drake Passage. This implies a ...